Pyramidalization of the glycosidic nitrogen provides the way for efficient cleavage of the N-glycosidic bond of 8-OxoG with the hOGG1 DNA repair protein - Šebera, Jakub; Trantírek, Lukáš; Tanaka, Yoshiyuki; Sychrovský, Vladimír (The journal of physical chemistry. B, 2012)
A mechanistic pathway for cleavage of the N-glycosidic bond of 8-oxo-2'-deoxyguanosine (oxoG) catalyzed with the human 8-oxoguanine glycosylase 1 DNA repair protein (hOGG1) is proposed in this theoretical study. The reaction scheme suggests direct proton addition to the glycosidic nitrogen N9 of oxoG from the Nε-ammonium of Lys249 residue of hOGG1 that is enabled owing to the N9 pyramidal geometry. The N9-pyramidalization of oxoG is induced within hOGG1 active site. The coordination of N9 nitrogen to the Nε-ammonium of Lys249 unveiled by available crystal structures enables concerted, synchronous substitution of the N9-C1' bond by the N9-H bond. The reaction is compared with other pathways already proposed by means of calculated activation energies. The ΔG(#) energy for the newly proposed reaction mechanism calculated with the B3LYP/6-31G(d,p) method 17.0 kcal mol(-1) is significantly lower than ΔG(#) energies for other reactions employing attack of the Nε-amino group to the anomeric carbon C1' of oxoG and attack of the Nε-ammonium to the N3 nitrogen of oxoG base. Moreover, activation energy for the oxoG cleavage proceeding via N9-pyramidalization is lower than energy calculated for normal G because the electronic state of the five-membered aromatic ring of oxoG is better suited for the reaction. The modification of aromatic character introduced by oxidation to the nucleobase thus seems to be the factor that is checked by hOGG1 to achieve base-specific cleavage.
Keywords: DNA-glykosylasy; glykosidy; deoxyguanosin; oprava DNA; DNA Glycosylases; Nitrogen; 8-hydroxy-2'-deoxyguanosin; Quantum Theory; lidé; Deoxyguanosine; DNA Repair; 8-Hydroxy-2'-Deoxyguanosine; Models, Molecular; molekulární modely; Glycosides; Thermodynamics; kvantová teorie; termodynamika; dusík; Humans